AL-MUSYKILÂT AL-TSAQÂFIYAH ALLATÎ TUJÂBAHU MUTA’ALLIMI AL-LUGHAH AL-‘ARABIYAH BI WASHFIHÂ LUGHAH TSÂNIYAH FÎ BILÂD AL-MALÂYÛ - Abdalla, Adil Elshiekh (Arabi : Journal of Arabic Studies, 2018)
The Arabic language that Malay learns as a second language belongs to a language group other than that of the Malay language, which is the mother tongue of the Arabic language learners in the Malay archipelago. It is well known that the Linguistic Library was filled with many studies comparing the two languages at the linguistic level, and no study compares them to the cultural level. Therefore, this pioneering study was concerned with a comparison between the two cultural languages. The study adopted a descriptive analytical approach; comparing the Malay and Arabic cultures and describing the differences between them in this field. The method of interviewing Malay students who represented the archipelago region and Arab Arabic teachers was also used to identify the most important problems arising from the different cultures that confront the two parties in Arabic teaching. The findings show that the Malay culture was greatly influenced by the Arab-Islamic culture. But there are differences between cultural manifestation in Arabic and Malay languages that, in turn, give some problems in Arabic teaching and learning in the Malay Archipelago.